Juegos motores y fundamentos técnicos de fútbol en estudiantes de primer grado de secundaria Colegio Cooperativo César Vallejo, Iquitos 2022 - Celis Vásquez, Luis Alberto (2023)
The objective of the study was to determine the relationship between motor games and the technical fundamentals of football in first grade high school students of the César Vallejo Cooperative School, Iquitos 2022. It is a descriptive research of correlational design, with a population and census sample of 125 students of the first grade of secondary education, to whom tests and registration forms were administered. The results showed that the level of mastery of motor games in students of the study sample was at the level not achieved (on average 49.0%) and in process (on average 35%). The level of mastery of the technical fundamentals of football in students was poor (on average 33.8%). The research concluded that there is a significant relationship between motor games and the technical foundations of football in first-grade high school students at the César Vallejo Cooperative School, Iquitos 2022.